Quantitative Characterization of Nut Yield and Fruit Components in Indigenous Coconut Germplasm in Sri Lanka. (17th August 2014) - Perera, S. A. C. N.; Dissanayaka, H. D. M. A. C.; Herath, H. M. N. B.; Meegahakumbura, M. G. M. K.; Perera, L.
Abstract : Coconut ( Cocos nucifera L.) is a tropical palm offering multiple uses. Conservation of coconut germplasm has been undertaken globally in view of its economic importance. This research was designed to evaluate nine Sri Lankan indigenous coconut germplasm representing the three varieties Typica, Nana, and Aurantiaca . Total annual nut yield and the weights of fresh nut, husked nut, split nut, and fresh and dry kernel were scored and analyzed with analysis of variance. The annual average number of bunches varied from 14.9 to 16.8 which is significantly higher than the generally accepted 12–14 bunches in tall coconuts. The high potential of phenotypes Ran thembili and Gon thembili for kernel production was revealed. The high potential of Gon thembili, Sri Lanka Tall, and Ran thembili to produce fibre was also identified. Phenotypes Ran thembili and Gon thembili displayed their potential as pure cultivars and as parents in hybridization. King coconut, Red dwarf, and Bodiri were shown to be suitable as beverage coconuts due to the high production of nuts, bunches, and the quantity of nut water. This study reiterated the importance of conservation and characterization of indigenous coconut varieties globally for their effective use in the genetic improvement of the coconut palm.